A creative tension between spirituality and physical needs : a theological Eccesiological evaluation of a food security programme for the council of churches in Zambia - Zulu, William (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.